2006
DOI: 10.4028/www.scientific.net/msf.518.325
|View full text |Cite
|
Sign up to set email alerts
|

SEM and XRD Characterization of Ni-Hf Alloys at Low Hf Concentration

Abstract: Abstract. The alloying and phase formation in Ni-Hf samples with 0.2-, 2-, and 5-at.% Hf were studied by X-ray diffraction (XRD) technique and scanning electron microscopy (SEM). Both characterization methods, XRD and SEM, reveal the presence of the HfNi 5 phase (fcc structure) where the excess Ni atoms are present in the form of Ni or Ni-rich segregations in the sample containing 5-at.% Hf. The sample with 2-at.% Hf is characterized by the presence of the two phases present in the 5-at.% sample and by Hf atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The rather large frequency distribution parameter ı 2 (18-51%) indicates a defect associated 181 Ta site. As seen from the previous experiments [11], distortions are present in the fcc HfNi 5 phase. Therefore, this EQI could be ascribed to Ta probe substituting in irregular HfNi 5 phase.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…The rather large frequency distribution parameter ı 2 (18-51%) indicates a defect associated 181 Ta site. As seen from the previous experiments [11], distortions are present in the fcc HfNi 5 phase. Therefore, this EQI could be ascribed to Ta probe substituting in irregular HfNi 5 phase.…”
Section: Resultsmentioning
confidence: 80%
“…To achieve a homogenous distribution of Hf, the sample was turned over and remelted several times. Our previous X-ray diffraction and scanning electron microscopy measurements confirmed alloying and phase formation in the Ni-Hf sample according to the Ni-Hf phase diagram [11]. Hf atoms occupy two different sites: substitutional lattice positions in Ni and in the HfNi5 phase with defective lattice structure relative to that of the equilibrium phase.…”
Section: Methodsmentioning
confidence: 82%
“…1. Previous SEM and XRD analysis of the nickel-5 at.% hafnium alloy revealed the presence of two phases: the Ni(Hf) solid solution and the defective HfNi 5 phases [1]. The majority of Hf atoms appeared to be incorporated in the HfNi 5 phase as demonstrated by EXAFS investigation on this alloy [1,2].…”
Section: Resultsmentioning
confidence: 93%
“…[1,2]. These earlier investigations on structural properties and alloy formation in the Ni-5 at.% Hf alloy showed that the composition of this alloy is in accordance with the Ni-Hf phase diagram [3].…”
Section: Methodsmentioning
confidence: 90%
“…The solid solubility of Hf in Ni is limited, and its maximum solubility below the eutectic temperature is estimated to be around 1.3 at.% [17]. In our earlier paper [18], we have performed comparative X-ray diffraction (XRD) and scanning electron microscopy (SEM) studies. Fig.…”
Section: D Elements Mo and Ru In Nimentioning
confidence: 99%